Outage and throughput performance of cognitive radio based power domain based multiple access - Dinh-Thuan Do; Chi-Bao Le (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2020)
This paper considers power domain based multiple access (PDMA) in cognitive radio network to serve numerous users who intend to multiple access to core network. In particular, we investigate the effect of signal combination scheme equipped at PDMA end-users as existence of direct link and relay link. This system model using relay scheme provides performance improvement on the outage probability of two PDMA end-users. We first propose a simple scheme of fixed power allocation to PDMA users who exhibit performance gap and fairness. Inspired by PDMA strategy, we then find signal to noise ratio (SNR) to detect separated signal for each user. In addition, the exact expressions of outage probability are derived in assumption that receiver can cancel out the interference completely with successive interference cancellation (SIC). By exploiting theoretical and simulation results, both considered combination schemes (Maximal Ratio Combining (MRC) and Selection Combining (SC) can achieve improved performance of two PDMA users significantly.